ANALISIS PUTUSAN HAKIM PENGADILAN AGAMA YANG MENGABULKAN GUGATAN PEMBATALAN PERKAWINAN (Studi Putusan Pengadilan Agama Tanjung Karang Nomor: 0174/Pdt.G/2020/PA.Tnk) - Jihan Al Litani; Mohamad Fajri Mekka Putra (The Juris, 2022)
The aim of this study is to determine the decision of the religious court judge who granted the marriage annulment lawsuit and the legal consequences of the religious court judge's decision which granted the marriage annulment lawsuit against the wife as the plaintiff. The research approach used is normative juridical law research or library research, with descriptive research type. The data analysis method used is qualitative. The results of this study indicate that the decision of the religious court judge who granted the marriage annulment suit was based on the existence of parties who could apply for the annulment of marriage, namely: a. Families in a straight line of descent from husband or wife; b. husband or wife; c. The authorized official only as long as the marriage has not been decided; d. Designated official. Article 22 of Law Number 1 of 1974 concerning Marriage states that the annulment of a marriage occurs because the parties do not meet the requirements to enter into a marriage. The reason for the annulment of the marriage is that the marriage was carried out under threats that violate the law and one of the parties falsifies his identity, for example falsifying age, status, and religion. The legal consequences of the decision of the religious court judge who granted the marriage annulment lawsuit against the wife as the plaintiff for the wife of the annulled marriage did not get the iddah subsistence right because since the cancellation decision was made from the court, the marriage was considered never to have occurred.